How frailty index impacts death in chronic kidney disease: A retrospective observational investigation - Mengmei Xiong; Xiaoyan Lu (PLoS ONE, 2026)
Background The present study assessed the link between the frailty index and deaths from all causes or specific causes in patients with chronic kidney disease (CKD). The study data were derived from the National Health and Nutrition Examination Survey (NHANES) (1999–2018) involving 3262 CKD patients. Methods We used 53 multifaceted assessment instruments to measure frailty degree. Multivariable Cox regression analysis was performed, and hazard ratio (HR) and 95% confidence interval (CI) were calculated. Results The median frailty index was 0.166 (interquartile range [IQR]: 0.01 to 0.665). During the median follow-up period of 9.4 years, a total of 1102 deaths from all causes were recorded, which included 196 cancer-related deaths and 402 heart disease-related deaths. Patients in the highest frailty index tertile showed more risk of dying from cardiovascular illness (adjusted HR 2.00, 95% CI 1.52–2.64), all causes (adjusted HR 1.81, 95% CI 1.54–2.13), and cancer (adjusted HR 1.59, 95% CI 1.09–2.33). The increase in cardiovascular-related deaths, all-cause-related deaths, and cancer-related deaths was 112% (P < 0.001), 85% (P < 0.001), and 72% (P < 0.001), respectively, for every logarithmic unit increase in the frailty index. These associations remained robust in stratified tests by sex, body mass index, age, race, diabetes history, hypertension status, and CKD stages. Conclusions Our findings suggest that among patients with CKD, the frailty index is linked to both cause-specific and all-cause deaths. A key element of managing CKD should be frailty intervention as the frailty index may indicate prognosis in these patients.